2010
DOI: 10.1099/vir.0.024430-0
|View full text |Cite
|
Sign up to set email alerts
|

Removal of transposon target sites from the Autographa californica multiple nucleopolyhedrovirus fp25k gene delays, but does not prevent, accumulation of the few polyhedra phenotype

Abstract: Low-cost, large-scale production of the baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV) using continuous insect cell culture is seriously hindered by the accumulation of AcMNPV mutants. Specifically, few-polyhedra (FP) mutants, with a reduced yield of occluded virus (polyhedra) and decreased infectivity, usually accumulate upon passaging in cell culture. FP mutations result from transposon insertions in the baculovirus fp25k gene, leading to significantly reduced levels of FP25K prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…Alphabaculovirus FP25Ks are thought to be partially responsible for the general switch between the production of BV and the production of ODV (14)(15)(16). In addition, infection with alphabaculovirus fp25k deletion mutants leads to the accumulation of BV envelope proteins like GP64 (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Alphabaculovirus FP25Ks are thought to be partially responsible for the general switch between the production of BV and the production of ODV (14)(15)(16). In addition, infection with alphabaculovirus fp25k deletion mutants leads to the accumulation of BV envelope proteins like GP64 (17).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid sequences of wild-type FP25K and both the D22P and L36P mutants were entered into the COILS server (http://www.ch.embnet.org/software/COILS_form.html), and the coiled-coil structure of these proteins was predicted (37). The output for this prediction is represented by graphical plots, with all residue-scanning windows (14,21,28) containing the probability of a coiledcoil structure based on similarity to structures in a database of known coiled-coil proteins. High-probability peaks in these plots indicate the likelihood of a coiled-coil structure in that region.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fp25k is a late cytoplasmic protein responsible for proper assembly and formation of polyhedra and acts as a switch from exporting BV to maintaining the virus within the cell, that is, ODV formation Saxena et al (2018). It has also been shown that a genetically modified virus with modified transposon insertion sites in the fp25k gene is capable of delaying the formation of FP mutant and defective interfering particle accumulation (Cheng et al, 2013; Giri et al, 2010). None of these studies, however, present a statistical model describing the structural variations present in infected cells, for example, the wide‐ranging polyhedra characteristics, ODV structures, and nucleocapsid packaging in ODVs, that result in a variety of phenotypes.…”
Section: Introductionmentioning
confidence: 99%